Description of a novel genus with three new species of Phoxocephalidae G. O. Sars, 1891 (Crustacea: Amphipoda) from off northeastern Brazil - Andrade, Luiz F.; Souza-Filho, Jesser F.; Senna, André R. (Zootaxa, 2022)
Magnaphoxus ajaja gen. et sp. nov., Ma. simplex gen. et sp. nov. and Ma. longicarpus gen. et sp. nov. are described. The material examined was collected off the states of Ceará, Rio Grande do Norte and Bahia during the projects “Avaliação da Biota Bentônica e Planctônica na porção offshore das Bacias Potiguar e Ceará (BPOT)” and “Programa de Avaliação do Potencial Sustentável de Recursos Vivos na Zona Econômica Exclusiva (REVIZEE)”. Additionally, material from other surveys off Brazilian northeastern coast is included. The samples were collected by rectangular dredges, box corer and Van Veen grabs, ranging from shallow waters to 168 meters in depth. The new genus is morphologically similar to the genera Grandifoxus Barnard, 1979, Metharpinia Schellenberg, 1931, Microphoxus Barnard, 1960 and Rhepoxynius Barnard, 1979. However, it can be recognized by the exclusive constricted and very broad rostrum and bilobated coxa 6, plus the combination of characters such as: lower lip outer plate with apical cusps; right mandible without lacinia mobilis; pereopods 3–4 carpus posterior margin with one distal robust long seta; propodus strongly armed with robust setae; uropods 1–2 peduncle dorsolateral margin combed distally; telson with two apical robust setae on each side. All three new species, are fully described, illustrated, and discussed.